1991
DOI: 10.1172/jci115007
|View full text |Cite
|
Sign up to set email alerts
|

New roles for rheumatoid factor.

Abstract: In the 1940s, anti-IgG autoantibodies were discovered in the sera of patients with rheumatoid arthritis and given the term rheumatoid factors (RF).' The measurement of agglutinating IgM-RF is still the most useful serological test for the diagnosis of rheumatoid arthritis. High titers of IgM-RF are also present in primary Sjogren's syndrome, mixed cryoglobulinemia, and in several different chronic infections (1).Recent advances in molecular and cellular immunology are gradually revealing the genetic and enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 45 publications
2
80
0
1
Order By: Relevance
“…B cells, however, are highly efficient in Ag presentation because they accumulate and incorporate Ag by specifically capturing them with their Ig receptors. This mechanism is particularly important for B cells with RF reactivity because RF-positive B cells bind immune complexes and process them for Ag presentation (18,25). They could, therefore, function as APCs in a cognate interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B cells, however, are highly efficient in Ag presentation because they accumulate and incorporate Ag by specifically capturing them with their Ig receptors. This mechanism is particularly important for B cells with RF reactivity because RF-positive B cells bind immune complexes and process them for Ag presentation (18,25). They could, therefore, function as APCs in a cognate interaction.…”
Section: Discussionmentioning
confidence: 99%
“…B cells may be superior to dendritic cells in capturing Ag, in particular, if Ag concentrations are limiting. B cells expressing Ig with RF activity could take up immune complexes presented by the follicular dendritic cells and thereby enrich for an infrequent Ag included in these complexes (18,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a low-affinity binding for multiple apparently unrelated antigens (reviewed in [6]), Several investigators propose a physiological role for these RF, They are thought to promote the clearance of circulating immune complexes (reviewed in [7]). RF-expressing B cells are considered to act as highly efficient antigen-presenting cells for low concentrations of immune-complexed antigen [8].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Many studies have reported that excess Il-6 were produced in inflammatory tissues related human disease such as rheumatoid arthritis, psoriasis, inflammatory bowel disease, osteoarthritis, and multiple myeloma. 4,5 It is also found in human atherosclerotic plaques, and is related to the impairment of endothelium-dependent dilatation in human veins.…”
mentioning
confidence: 99%